Motor transport development in Klaipėda district in 1900-1939 - Julius Žukas (Lietuvos Istorijos Studijos)
The first car in Klaipėda District (Memelgebiet) appeared in 1900, while motor transport started to spread from the 3rd decade of the XX century. In the beginning of 1920, there were 49 cars registered in the district, in 1922, 108 cars registered, while by the end of 1928 - 307 cars registered. The most popular were passenger cars, whereas buses were the latest to appear and the least widespread. At the end of 1937, there were 390 passenger cars, 99 trucks, and 40 buses registered in the district. Most of the cars were registered in Klaipėda city. Compared to the Lithuanian Republic, the degree of motor transport prevalence in Klaipėda district was greater: in 1938 there were 903 residents per one car in Lithuania and 222 residents per one car in the Klaipėda district.